Noninvasive mechanical destruction of liver tissue and tissue decellularisation by pressure-modulated shockwave histotripsy - Pahk, Ki Joo; Heo, Jeongmin; Joung, Chanmin; Pahk, Kisoo (Frontiers in Immunology, 2023)
Introduction Boiling histotripsy (BH) is a promising High Intensity Focused Ultrasound (HIFU) technique that can be used to mechanically fractionate solid tumours at the HIFU focus noninvasively, promoting tumour immunity. Because of the occurrence of shock scattering phenomenon during BH process, the treatment accuracy of BH is, however, somewhat limited. To induce more localised and selective tissue destruction, the concept of pressure modulation has recently been proposed in our previous in vitro tissue phantom study. The aim of the present study was therefore to investigate whether this newly developed histotripsy approach termed pressure-modulated shockwave histotripsy (PSH) can be used to induce localised mechanical tissue fractionation in in vivo animal model. Methods In the present study, 8 Sprague Dawley rats underwent the PSH treatment and were sacrificed immediately after the exposure for morphological and histological analyses (paraffin embedded liver tissue sections were stained with H&E and MT). Partially exteriorised rat’s left lateral liver lobe in vivo was exposed to a 2.0 MHz HIFU transducer with peak positive (P+) and negative (P-) pressures of 89.1 MPa and –14.6 MPa, a pulse length of 5 to 34 ms, a pressure modulation time at 4 ms where P+ and P- decreased to 29.9 MPa and – 9.6 MPa, a pulse repetition frequency of 1 Hz, a duty cycle of 1% and number of pulses of 1 to 20. Three lesions were produced on each animal. For comparison, the same exposure condition but no pressure modulation was also employed to create a number of lesions in the liver. Results and Discussion Experimental results showed that a partial mechanical destruction of liver tissue in the form of an oval in the absence of thermal damage was clearly observed at the HIFU focus after the PSH exposure. With a single pulse length of 7 ms, a PSH lesion created in the liver was measured to be a length of 1.04 ± 0.04 mm and a width of 0.87 ± 0.21 mm which was 2.37 times in length (p = 0.027) and 1.35 times in width (p = 0.1295) smaller than a lesion produced by no pressure modulation approach (e.g., BH). It was also observed that the length of a PSH lesion gradually grew towards the opposite direction to the HIFU source along the axial direction with the PSH pulse length, eventually leading to the generation of an elongated lesion in the liver. In addition, our experimental results demonstrated the feasibility of inducing partial decellularisation effect where liver tissue was partially destructed with intact extracellular matrix (i.e., intact fibrillar collagen) with the shortest PSH pulse length. Taken together, these results suggest that PSH could be used to induce a highly localised tissue fractionation with a desired degree of mechanical damage from complete tissue fractionation to tissue decellularisation through controlling the dynamics of boiling bubbles without inducing the shock scattering effect.